Opportunities for CO2 upgrading to C3 oxygenates using tandem electrocatalytic-thermocatalytic processes - Samay Garg; Akash N. Biswas; Jingguang G. Chen (Carbon Future)
Catalytic conversion of CO2 to value-added chemicals represents a pathway for mitigating CO2 emissions. Many recent studies have demonstrated promising results of CO2 conversion by either thermocatalysis or electrocatalysis. In this article, we discuss tandem electrocatalytic-thermocatalytic processes that potentially have advantages over either process alone. We use the conversion of CO2 to propanal/propanol as a case study to illustrate the feasibility of the tandem process. We also discuss opportunities and challenges for converting CO2 using tandem electrocatalytic-thermocatalytic approaches.